Industrialization and national prosperity: lessons for the developing countries - Ekeh, Lawrence U (London: Luzek Publishers, 2009)
The book provides not only a historical perspectives, but uncovers present development obstacles with giving solutions for Developing Countries.
Includes indexes and bibliographical references.
lje 9/9/13
Loans
Keywords: Industrialization -- Developed countries -- Case studies; Economic development; Industrial policy; Industrialization -- Developing countries